The use of oral topically acting glucocorticosteroids in the treatment of inflammatory bowel disease - P. Rutgeerts (Mediators of Inflammation)
Glucocorticosteroids are the mainstay of treatment of active Crohn's disease and ulcerative colitis. These drugs however carry important cosmetic short-term side effects and when used long-term they induce severe irreversible complications. Topically acting glucocorticosteroids, especially budesonide, have been designed to achieve local effect at the site of inflammation without systemic effects of the drug. The first results of clinical trials are promising and budesonide has been shown to have an improved safety with almost comparable efficacy in comparison with prednisolone. The optimal enema dose seems to be 2 mg/100 ml at night whereas 9 mg o.m. is the optimal dose to treat ileal or right ileocolonic Crohn's disease. Topically acting GCS, like standard GCS are not effective for maintenance of remission of Crohn's disease or recurrence prevention after resection of the involved Crohn's segment.